COPING WITH LANGUAGE BARRIERS: A NARRATIVE STUDY OF TEACHING ENGLISH AT A THAI SCHOOL - Vioni Putri Ismida; Atin Kurniawati (Vol. 3 No. 2 (2025): Special Issue: Cultural Resilience and Digital Literacy for a Diverse Society)
Language barriers are significant issues that can hinder clear communication between individuals. They are major sources of many problems or challenges in the fields of business, education, aviation, maritime, and healthcare. In education, language barriers pose a challenge for a pre-service English teacher involved in cross-cultural teaching activities. This study aims to analyze the different types of language barriers that may occur and explore strategies that can be used to overcome these language barriers. This study used a narrative inquiry research strategy to explore the pre- service English teacher's experiences and perspectives on the phenomenon under study. The data in this study were obtained from a pre-service English teacher by conducting open-ended questionnaires and interviews. The data analysis used the theory of Miles and Huberman which includes three main stages: data reduction, data display or data presentation, and drawing a conclusion or verification. The data findings revealed that a pre-service English teacher faced significant language barriers, such as mispronunciation, grammar errors, and vocabulary limitations. Despite these language barriers, the pre-service English teacher also found some strategies such as effective communication strategies, automatic translation technology, and translator assistance. It implies that a pre-service English teacher needs to equip themselves with strategies to cope with communication barriers for any situation during their teaching context.